Enzymatic hydrolysis and ion exchange fractionation of sulfated polysaccharides extracted from Ulva lactuca and evaluation of their biological activity. - Abou El Azm, Nihal Ali Moheib Abdelmoneim (AUC Knowledge Fountain, 2016)
Sulfated polysaccharides (SPs) were extracted from the green algae, Ulva lacutca. High molecular weight SPs were enzymatically hydrolysed using viscozyme then fractionated into 8 different molecular weight fractions by means of diethyl amino ethyl (DEAE) anion exchange column chromatography. Crude SPs together with the hydrolysate and the 8 column effluent fractions were tested for their carbohydrate, protein and sulfate contents. In addition, their degree of polymerization (D.P.) was estimated and they were characterized by Fourier Transform Infrared Spectroscopy (FTIR). Their antioxidant and antitumor activities were also determined using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide) (MTT) assays, respectively. Four types of cancer cell lines were investigated, namely, HCT116 (Colon cell line), A549 (Lung carcinoma cell line), HePG2 (Human hepatocellular carcinoma cell line) and MCF7 (Breast carcinoma cell line). The study showed that S1 (crude SPs), F2-F5 (from second to the fifth fractions eluted from the column) as well as F8 (eighth fraction eluted from the column) exhibited high antioxidant activity reaching above 60%. The highest activity was for S1, above 65%, which indicates that the antioxidant activity was not improved by hydrolysis and fractionation. As for the antitumor activity, S1, F4, F5 and F8 showed promising antitumor activity by causing a lethality death above 75% at 100 ppm. F5 showed the best antitumor activity as it gave promising results on three types of cancer cell lines; A549, HePG2 and MCF7 while F4, F8 and S1 gave promising results on one type of cell line, HePG2, MCF7 and HCT116 respectively. The most common feature of S1, F4, F5 and F8 is that they all have approximate carbohydrate to sulfate ratio of 1, which indicates that this ratio has an important effect on the biological activity. Also sugar analysis for S1, F4, F5 and F8 revealed that higher glucuronic acid in lower D.P. together with average rhamnose improve biological activity and vice versa in higher D.P.. Other influencing factors include D.P., composition, type and arrangement of characteristic functional groups like sulfate, hydroxyl and amide as well as polymer complexity and monomer distribution and branching. Sugar analysis for the antitumor active S1, F4, F5 and F8 revealed that glucuronic acid and rhamnose contents could affect the activity.